The impact of sports event-brand fit on consumer brand responses: a meta-analytic review - Liu, Qingfeng; Liu, Bing (Frontiers in Sports and Active Living, 2025)
IntroductionIn an era where global sports sponsorship is prevalent, companies aim to gain market share through sports sponsorship. Existing research typically examines this phenomenon by assessing consumer responses; however, different studies have yielded inconsistent or even contradictory findings.MethodsThis study employs a meta-analytic approach to synthesize previous research, examining the impact of sports event-brand fit on consumers' cognitive, emotional, and behavioral responses, as well as the moderating effects of factors such as gender, sample source, and context type. The analysis includes 57 effect sizes from 31 studies, encompassing a total of 15,744 participants.ResultsSports event-brand fit has a positive effect on consumers' cognitive, emotional, and behavioral response. Moreover, sample sources and context types partially moderated these relationships, while gender showed no significant effect.DiscussionFindings suggest that sponsoring brands should align their sports sponsorships with specific developmental goals. Additionally, when sponsoring sports events in other countries, brands should respect cultural differences and tailor their marketing strategies to suit different contexts.Systematic Review Registrationhttps://www.prisma-statement.org